Aesthetic and cultural aspect of ancient art in context of dialogue man is the world Other - Volodymyr Fed; Angelina Koshel (Cхід, 2016)
The article is sanctified to the comprehension of artistic heritage of Antiquity from the point of view of opening of dialogic intercommunication a "man is the world Other", that most full determined the world view of that time man, his aesthetic taste and lined up a cultural paradigm on the whole. The collisions of development of globalization us to appeal to the art of the past with the purpose of making of new imperatives of the system "A man is the world Other", actual in the epoch of Post-modern. In particular, an ancient art teaches to beauty and harmony with the world Other, that it can be fixed in basis of development of ecological consciousness that is beyond an ethic relation in an area aesthetic. For the art of Post-modern Antiquity can become the отправным point of revival of spirituality and dialogue with the world Other on principles of Truth, Beauty and Good.An ancient art must not be "a pariah" in the design of cultural existence of modern man; it can become the point of revival of spirituality and dialogue with the world Other on principles of Truth, Beauty and Good.